2009
DOI: 10.1021/ja808099u
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of a Tetraanionic Porphyrin with DNA: from a Z-DNA Sensor to a Versatile Supramolecular Device

Abstract: The anionic nickel(II) porphyrin NiTPPS is able to selectively sense the spermine induced left-handed Z-form of DNA while it is completely silent in the presence of right-handed B-DNA. Interactions between the DNA and the porphyrin can be easily modulated by pH and temperature. The resulting Z-DNA-porphyrin-spermine complex behaves as a supramolecular reversible information storage system and as a reversible AND logic gate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 23 publications
0
72
0
Order By: Relevance
“…It was shown that out of water-soluble tetra-cationic 5,10,15‚20-tetra(N-methylpyridinium-4-yl)porphyrin (TMPyP) naturally drawn to the DNA polyanion, tri-or dicationic derivatives also bind to DNA by intercalation or by external binding (Pasternack et al 1983;Shui et al 2000;Zupan et al 2004;D'Urso et al 2009;Gong et al 2012;Accetta et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that out of water-soluble tetra-cationic 5,10,15‚20-tetra(N-methylpyridinium-4-yl)porphyrin (TMPyP) naturally drawn to the DNA polyanion, tri-or dicationic derivatives also bind to DNA by intercalation or by external binding (Pasternack et al 1983;Shui et al 2000;Zupan et al 2004;D'Urso et al 2009;Gong et al 2012;Accetta et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins are also one of the most studied DNA binding agents [6,7]. The binding of cationic porphyrin derivatives to nucleic acids has been the subject of extensive research since Fiel and colleagues discovered that these compounds can form various complexes with DNA [8].…”
Section: Introductionmentioning
confidence: 99%
“…There are two recent reports wherein porphyrins are used to distinguish between these two types of DNA. 55,56 In 2005, Purrello and coworkers reported the pentacoordinated cationic zinc-porphyrin-based chiroptical probe, 23·H 2 O, and demonstrated its ability to discriminate between B and Z structures. A desirable chiroptical probe is one that absorbs above 300 nm-an area free from interference of most biological species.…”
Section: Dnamentioning
confidence: 99%